2020
DOI: 10.1136/bmjopen-2020-040641
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of sociocultural factors influencing intimate partner violence among young women in sub-Saharan Africa: a scoping review

Abstract: ObjectiveThis study carried out a scoping review of research on intimate partner violence to determine the extent to which studies on sociocultural factors influencing intimate partner violence among young women (15–24 years) have been conducted, and how different geographical areas are represented. It also considered whether the methodologies used were sufficient to describe the risk factors, prevalence and health outcomes associated with intimate partner violence among young women.Study designScoping review.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
(73 reference statements)
0
11
0
Order By: Relevance
“…The MMAT critical appraisal tool allows for the examination of methodological and conceptual design components of qualitative, quantitative, and MM research studies (Hong et al, 2019; Maguele et al, 2020). Two authors (A. G. and C. R. S.) independently assessed the quality of each study and then jointly discussed quality appraisal results to determine whether articles should be included.…”
Section: Methodsmentioning
confidence: 99%
“…The MMAT critical appraisal tool allows for the examination of methodological and conceptual design components of qualitative, quantitative, and MM research studies (Hong et al, 2019; Maguele et al, 2020). Two authors (A. G. and C. R. S.) independently assessed the quality of each study and then jointly discussed quality appraisal results to determine whether articles should be included.…”
Section: Methodsmentioning
confidence: 99%
“…An earlier study observed similar risk factors for IPV among young women, namely, discrepancy in education level between partners and low economic status; unemployment; alcohol consumption by partner; and history of violence, including child violence experienced by both partners, as well as male‐dominated social norms/rules and legal systems. However, these authors warned that, even with a diversity of factors, it is still not possible to understand the phenomenon, as there are few studies that assess the sociocultural influence on IPV (Maguele et al, 2020). Thus, this study reflects the greater complexity when assessing IPV against indigenous women, as studies with this specific population are scarce and difficult to compare from a sociocultural point of view.…”
Section: Discussionmentioning
confidence: 99%
“…The mentioned guideline is a unique, efficient appraisal tool focused on the methodology criteria of different study designs simultaneously [ 50 ]. For this reason and given that this quality assessment tool has been applied to systematic reviews related to the intimate partner violence topic [ 52 , 53 , 54 ], it has been selected for the quality assessment. Two researchers assessed the quality of each study, and a third one resolved discrepancies.…”
Section: Methodsmentioning
confidence: 99%